Technical Comparison of Treatment Efficiency of Magnetic Resonance-Guided Focused Ultrasound Thalamotomy and Pallidotomy in Skull Density Ratio-Matched Patient Cohorts - Ahmed, Abdul-Kareem; Guo, Sijia; Kelm, Nathaniel; Clanton, Ryan; Melhem, Elias R.; Gullapalli, Rao P.; Ksendzovsky, Alexander; Eisenberg, Howard M.; Miller, Timothy R.; Gandhi, Dheeraj (Frontiers in Neurology, 2022)
Objective MR-guided focused ultrasound (MRgFUS) is increasingly being used to treat patients with essential tremor (ET) and Parkinson's disease (PD) with thalamotomy and pallidotomy, respectively. Pallidotomy is performed off-center within the cranium compared to thalamotomy and may present challenges to therapeutic lesioning due to this location. However, the impact of target location on treatment efficiency and ability to create therapeutic lesions has not been studied. This study aimed to compare the physical efficiency of MRgFUS thalamotomy and pallidotomy. Methods Treatment characteristics were compared between patients treated with thalamotomy (n = 20) or pallidotomy (n = 20), matched by skull density ratios (SDR). Aspects of treatment efficiency were compared between these groups. Demographic and comparative statistics were conducted to assess these differences. Acoustic field simulations were performed to compare and validate the simulated temperature profile for VIM and GPi ablation. Results Lower SDR values were associated with greater energy requirement for thalamotomy (R2 = 0.197, p = 0.049) and pallidotomy (R2 = 0.342, p = 0.007). The impact of low SDR on efficiency reduction was greater for pallidotomy, approaching significance (p = 0.061). A nearly two-fold increase in energy was needed to reach 50°C in pallidotomy (10.9kJ) than in thalamotomy (5.7kJ), (p = 0.002). Despite lower energy requirement, the maximum average temperature reached was higher in thalamotomy (56.7°C) than in pallidotomy (55.0°C), (p = 0.017). Mean incident angle of acoustic beams was lesser in thalamotomy (12.7°) than in pallidotomy (18.6°), (p < 0.001). For all patients, a lesser mean incident angle correlated with a higher maximum average temperature reached (R2 = 0.124, p = 0.026), and less energy needed to reach 50°C (R2=0.134, p = 0.020). Greater skull thickness was associated with a higher maximum energy for a single sonication for thalamotomy (R2 = 0.206, p = 0.045) and pallidotomy (R2 = 0.403, p = 0.003). An acoustic and temperature field simulation validated similar findings for thalamotomy and pallidotomy in a single patient. Conclusion The centrally located VIM offers a more efficient location for therapeutic lesioning compared to GPi pallidotomy in SDR matched cohort of patients. The impact on therapeutic lesioning with lower SDR may be greater for pallidotomy patients. As newer off-center targets are investigated, these findings can inform patient selection and treatment requirements for lesion production.